Financial Globalisation Dynamic Thresholds for Financial Development: Evidence from Africa. Issue 1 (January 2017) - Asongu, Simplice A; De Moor, Lieven
Abstract We investigate whether financial development benefits from financial globalisation are questionable until certain thresholds of financial globalisation are attained. The empirical evidence is based on (i) data from 53 African countries for the period 2000–2011 and (ii) interactive Generalised Method of Moments with forward orthogonal deviations. The following findings are established. First, thresholds of Net Foreign Direct Investment Inflows as a percentage of GDP (FDIgdp) from which financial globalisation increases money supply are 20.50 and 16.00 for below- and above-median sub-samples of financial globalisation, respectively. Second, FDIgdp thresholds from which financial globalisation increases banking system activity and financial system activity for below-median sub-samples of financial globalisation are 13.81 and 13.29, respectively. Third, for financial size, there is evidence of: (i) a positive threshold of 21.30 in the full sample and (ii) consistent increasing returns without a modifying threshold for the above-median sub-sample. Policy implications are discussed. Abstract Nous faisons une enquête pour savoir si les avantages au développement financier de la mondialisation financière sont contestables jusqu'à ce que certains seuils de la mondialisation financière soient atteints. Les données empiriques sont fondées sur; (i) les données de 53 pays africains pour la période 2000–2011 et (ii) la Méthode interactive des Moments Généralisés avec des déviations orthogonales avants. Les résultats suivants sont avérés. Tout d'abord, les seuils des entrées nettes d'investissements direct à l'étranger en pourcentage du PIB (IDE Pib), à partir desquels la mondialisation financière augmente la masse monétaire, sont respectivement en dessous et au-dessus de la médiane de 20, 50 et 16, 00 des sous-échantillons de la mondialisation financière. Ensuite, les seuils IDE Pib, à partir desquels la mondialisation financière augmente l'activité du système bancaire et l'activité du système financier, sont respectivement de 13, 81 et 13, 29. Enfin, en ce qui concerne le volume financier, il y a des preuves de: (i) un seuil positif de 21, 30 à l'ensemble de l'échantillon et (ii) rendements croissants réguliers sans modification du seuil pour les sous-échantillons au-dessus de la médiane. Les retombées politiques sont discutées.